Graphic design : now in production - Blauvelt, Andrew; Lupton, Ellen; Giampietro, Rob; Walker Art Center (Minneapolis [Minn.] : Walker Art Center, 2011)
- The designer as producer / Ellen Lupton##- Fuck content / Michael Rock##- Research and destroy : design as investigation / Daniel van der Velden##- Unraveling / Lorraine Wild##- Tool (or, postproduction for the graphic designer) / Andrew Blauvelt##- Design entrepreneur 3.0 / Steven Heller##- Practice from everyday life : defining graphic design's expansive scope by its quotidian activities / James Goggin##- Reading and writing / Ellen Lupton##- Magazine culture / Jeremy Leslie##- The persistence of posters / Andrew Blauvelt##- The making of typographic man / Ellen Lupton##- Experimental typography. Whatever that means. Conceptual type? / Peter Bil'ak##- Design in motion / Ben Radatz##- The art of the title sequence / Ian Albinson##- I am still alive #21 / Åbäke##- Bubbles, lines, and string : how information visualization shapes society / Peter Hall##- Brand matrix / Armin Vit and Bryony Gomez-Palacio##- Brand new worlds / Andrew Blauvelt##- Designing our own graves / Dmitri Siegel##- School days / Rob Giampietro.
Published on the occasion of an exhibition held at the Walker Art Center, Minneapolis, Minn. and four other institutions between Oct. 22. 2011 and Dec. 2013.
boek